Potret Pendidikan di Desa Sebangun Kecamatan Sebawi Kabupaten Sambas - Sarbini, Sarbini (Universitas Tanjungpura, 2024)
The purpose of this research is to describe the state of education in Sebangun Village, Sambas Regency. This study examines the facts, challenges, and solutions employed to address educational issues faced by the community in Sebangun Village. A qualitative method with a descriptive approach was used, involving data collection through observations, interviews, and document studies, as well as direct and open observation and interview guidelines. The research informants consist of school principals and teachers from elementary to high school levels, as well as the local community of Sebangun Village. Therefore, the population of this study includes educational institutions and the community of Sebangun Village. Data analysis follows the Milles and Huberman model, involving a process that culminates in drawing conclusions and validating data through extended observations, source triangulation, and document studies. The results reveal that education in Sebangun Village still faces significant challenges. The school facilities and infrastructure are inadequate, with many damaged facilities and a lack of proper learning aids. Additionally, students' low motivation to learn is another inhibiting factor, influenced by the parents' economic conditions and the lack of community support. The study also found that the quality of educators needs improvement, as many teachers do not have a bachelor's degree (S1/D4). The community's low awareness of the importance of education and the low rate of student participation in pursuing higher education are also contributing factors. To improve the quality of education, collaboration is needed between the village, district, and provincial governments, as well as active involvement from the community in supporting children's education programs in Sebangun Village. Through appropriate steps, it is hoped that this research will contribute to significant improvements in education in Sebangun Village and have a positive impact on the community as a whole.